Evaluation of urinary continence status and its influence on quality of life after gyneco-oncological treatment of female pelvic malignancies at an oncological center - Maryam Zafarnia; Lieven N. Kennes; Elmar Stickeler; Johannes Hoff; Laila Najjari (BMC, 2022)
Abstract Urinary incontinence (UI) could negatively affect a person's quality of life (QoL). This study investigates the association among gynecological cancers, their treatments, UI, and its effect on the QoL of survivors of gynecological cancer. This cross-sectional questionnaire-based study included 121 cases from 405 patients who had undergone gyneco-oncological therapy. The participants were asked whether they experienced any form of UI and whether it impacted their QoL. The following therapies were used to treat the 12 gynecologic tumor types found in the participants: surgery (n = 116, 95.87%), chemotherapy (CTx) (n = 51, 42.2%), radiotherapy (RTx) (n = 31, 25.6%), and antibody therapy (ABT) (n = 11, 9.1%). No significant association was determined between tumor type and UI. However, body mass index (BMI), radical hysterectomy, vulvar or vaginal surgery, and presence of UI before treatment had significant impacts on the presence of UI. The surgical access routes, CTx, ABT, and hysterectomy had significant impacts on the severity of UI after treatment. Among all patients, 55.4% reported very good QoL. These reports of good QoL by patients could be due to their very good adjustment to the situation, with regard to being diagnosed with and receiving treatment for cancer, or due to the patients considering UI to not be much of an issue. Additionally, 34% of patients reported they had not been informed about the risk of UI before treatment. Informing patients about UI as one of the risks of therapy before initiating the treatment is crucial as patients who had been informed beforehand coped with UI far better than those who were not informed. Hence, the treatment of UI is often successful, so patients should be encouraged to receive urogynecological consultation.